Ultrasound Diagnosis of Pneumothorax in Blunt Chest Trauma: A Correlation Study with Computed Tomography Thorax in Emergency Department Patients at Tertiary Care Centre in Salem, Tamil Nadu - Syed Abthahir Sirajudeen; Melvin Dominic; VK Sreelakshmi; Moturi Sai Vineeth; Pooja Rani; Jinka Venakata Durgaprasad; Senthil Kumar Manickam; P Panneerselvam (Journal of Pharmacy and Bioallied Sciences)
Introduction: In this study, we compared lung ultrasonography (USG) and computed tomography (CT) findings of the thorax in diagnosing pneumothorax in patients with blunt chest trauma. This study aimed to improve diagnostic accuracy and prevent tension pneumothorax, despite limited evaluations across all lung pathologies. Methods: We examined patients admitted to Kirupananda Variyar Medical College and Hospital with blunt chest trauma from January 2021 to June 2022. Lung USG and CT of the chest were used to detect pneumothoraxes, with the goal of reducing mortality rates in severely injured patients. Results: Out of 64 cases, 67.5% experienced blunt trauma, 20.8% had a direct chest impact, and 11.7% suffered falls from a height. USG and CT findings revealed the following: 79.2% had pneumothorax, 7.8% had pleural effusion, 28.6% had hemothorax, 22.1% had contusion, 10.4% had rib fractures with contusion, 6.5% had rib fracture + Hemothorax, and 9.1% had isolated pneumothorax. Conclusion: Lung ultrasound is a reliable, radiation-free method for assessing pneumothorax, pleural effusion, contusion, and hemothorax, offering a definitive, sensitive, and accurate diagnosis.